Development of Intermediate Cooling Technology and Its Control for Two-Stand Plate Rolling - Fei Zhang; Wei Yu; Tao Liu (Journal of Control Science and Engineering)
In a plate rolling production line, thermomechanically controlled processing is critical for plate quality. In this paper, a set of intermediate cooling equipment of a two-stand plate mill with super density nozzles, medium pressure, and small flow is developed. Based on a simplified dynamic model, a cooling control scheme with combined feedforward, feedback, and adaptive algorithms is put forward. The new controlled rolling process and the highly efficient control system improve the controlled rolling efficiency by an average of 17.66%. The proposed intermediate cooling system can also effectively inhibit the growth of austenite grain, improve the impact toughness and yield strength of Q345B steel plate, reduce the formation of secondary oxide scale on the plate surface and the chromatic aberration of the plate surface, and greatly improve the surface quality of the steel plate.